Comparison of the potency of three Brazilian Bothrops antivenoms using in vivo rodent and in vitro assays. BIASG (Butantan Institute Antivenom Study Group). - Laing, G; Theakston, R; Leite, R; da Silva, W; Warrell, D (1992)
Three Brazilian polyspecific Bothrops antivenoms were compared using standard W.H.O. rodent in vivo and in vitro assays of their ability to neutralize the principal venom activities of pooled whole Bothrops jararaca venom. On a volume basis, the antivenoms were equally effective in neutralizing lethal activity in mice, and there were only minor differences in their ability to neutralize venom-induced haemorrhage, necrosis and procoagulant activity. Antivenom efficacy in neutralizing defibrinogenation varied. However, when equal amounts of antivenom IgG were compared, it was found that the FUNED antivenom best neutralized lethality, haemorrhage, necrosis and fibrinogen clotting activity. Vital Brazil and FUNED antivenoms were equally effective in neutralizing plasma coagulant activity but Vital Brazil antivenom was the more effective in neutralizing defibrinogenation.